Will rural urbanization produce a new producer service space in China?. (September 2017) - Yeh, Anthony G.O.; Yang, Fiona F.; Xu, Zhihua
Abstract: The spatial relationship between manufacturing and producer services is being significantly weakened in advanced economies because of the decline of manufacturing industries. However, as upstream–downstream industries, manufacturing and producer services have incentives to locate in proximity to each other. In developing countries, such as China, where manufacturing is still an important component of the economy, the evolution of the manufacturing–services relationship and its link to the distribution of producer services have remained unclear. After the economic reforms in 1978, China has experienced a distinctive process of rural industrialization and town development. Will a new producer service space, which is different from that of developed and other developing countries, be produced in China given its development of rural industries? We examine this question by using Guangdong Province, one of China's manufacturing bases and representative regions of rural industrialization, as a case study. Our findings suggest that despite their close input–output linkage, manufacturing and producer services are less likely to co-locate. The development of rural industries has not reduced the importance of large cities and city centers in producer service development. The accelerated economic globalization, the rapid growth of the service sector, and the low-end nature of rural industries have made the manufacturing–services linkage less crucial in determining the location of producer services. Highlights: We examine the spatial linkage between manufacturing and producer services. Manufacturing is still an important component of developing economies. Guangdong Province in southern China is used as a case study. Rural industrialization has not led to dispersed producer service development. Producer service development is determined more by other sources of externalities.